Análise do conversor bridgeless boost PFC integrado aplicado na iluminação de estado sólido - Fernandes, Iane Andrade (2017)
In this work, the integrated Bridgeless Boost PFC converter employing an asymmetrical switching strategy for driving power LEDs lighting systems is presented. The use of polypropylene capacitors in the DC bus in the circuit, helps to increase the useful life of the converter. First this study involves a brief contextualization of the subject, followed by an analysis of the circuit proposed in this dissertation and its mathematical modeling. The direct current (350mA) applied to the LEDs in this topology is obtained through a rectifier bridge with a capacitive filter connected between the inverter stage and the center point of the two capacitors of the DC bus. In order to verify the analyses carried out, computer simulations and experimental results for 35 LEDs and 42 W using three different switching frequency values are presented.